Cytogenetic mapping and contribution to the knowledge of animal genomes - Martins, Cesar [UNESP]; Cabral-de-Mello, Diogo Cavalcanti [UNESP]; Valente, Guilherme Targino [UNESP]; Mazzuchelli, Juliana [UNESP]; de Oliveira, Sarah Gomes [UNESP] (My University, 2011)
Decades before the recent advances in molecular biology and the knowledge of the complete nucleotide sequence of several genomes, cytogenetic analysis provided the first information concerning the genome organization. Since the beginning of cytogenetics, great effort has been applied for understanding the chromosome evolution in a wide range of taxonomic groups. The exploration of molecular biology techniques in the cytogenetic area represents a powerful tool for advancement in the construction of physical chromosome maps of the genomes. The most important contribution of cytogenetics is related to the physical anchorage of genetic linkage maps in the chromosomes through the hybridization of DNA markers onto chromosomes. Several technologies, such as polymerase chain reaction (PCR), enzymatic restriction, flow sorting, chromosome microdissection and BAC library construction, associated with distinct labeling methods and fluorescent detection systems have allowed for the generation of a range of useful DNA probes applied in chromosome physical mapping. Concerning the probes used for molecular cytogenetics, the repetitive DNA is amongst the most explored nucleotide sequences. The recent development of bacterial artificial chromosomes (BACs) as vectors for carrying large genome fragments has allowed for the utilization of BACs as probes for the purpose of chromosome mapping. BACs have narrowed the gap between cytogenetic and molecular genetics and have become important tools for visualizing the organization of genomes and chromosome mapping. Furthermore, the use of chromosome probes has permitted the development of chromosome painting technologies, allowing an understanding of particular chromosomal areas, whole chromosomes or even whole karyotypes. Moreover, chromosomal analysis using these specific probes has contributed to the knowledge of supernumerary chromosomes, sex chromosomes, species evolution, and the identification of chromosomal rearrangements. Finally, the synergy between chromosomal and molecular biology analysis makes cytogenetics a powerful area in the integration of knowledge in genetics, genomics, taxonomy and evolution.